Combatting chemoresistance: an analysis of DNA repair proteins ERCC1 and XPF and their chemotherapeutic implications in ovarian cancer - Griffin, Michaela (2019)
Platinum-based drugs form a key aspect of multimodal treatment to various cancers. Despite this, resistance to platinum therapy is a colossal threat encircling the treatment of ovarian cancers. It is well documented that an upregulation in DNA repair pathways is an advantageous characteristic for cancer cells and results in the emergence of chemoresistance. Nucleotide excision repair (NER) is essential in the DNA damage response (DDR) and removes bulky DNA adducts caused primarily by UV light. This pathway utilises Xeroderma Pigmentosum F (XPF) and Excision Repair Cross-Complementation Group 1 (ERCC1) endonucleases in the final cleavage of the 5’ DNA lesion. An intact nucleotide excision repair (NER) pathway is required for the correction of platinum-induced crosslinks; cells lacking functional NER show exquisite sensitivity to platinum agents.